Long Non-coding RNA Expression Patterns in Stomach Adenocarcinoma Serve as an Indicator of Tumor Mutation Burden and Are Associated With Tumor-Infiltrating Lymphocytes and Microsatellite Instability - Yang, Dongdong; Yu, Jinling; Han, Bing; Sun, Yue; Mo, Steven; Hu, Jing (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) are crucial in controlling important aspects of tumor immunity. However, whether the expression pattern of lncRNAs in stomach adenocarcinoma (STAD) reflects tumor immunity is not fully understood. We screened differentially expressed lncRNAs (DElncRNAs) from STAD samples in The Cancer Genome Atlas with high or low tumor immunogenicity, measured as tumor mutation burden. Using the least absolute shrinkage and selection operator method, 33 DElncRNAs were used to establish a lncRNA-based signature classifier for predicting tumor mutation burden. The accuracy of the 33-lncRNA-based signature classifier was 0.970 in the training set and 0.950 in the test set, suggesting the expression patterns of the 33 lncRNAs may be an indicator of tumor mutation burden in STAD. Survival analysis showed that a lower classifier index reflected better prognosis for STAD patients, and the index showed weak correlation with expression of immune checkpoint molecules (PDCD1, CD274 and CTLA4) and tumor-infiltrating lymphocytes. In conclusion, STAD samples with different tumor mutation burdens have different lncRNA expression patterns. The 33-lncRNA-based signature classifier index may be an indicator of tumor immunogenicity and may be associated with other factors predicting the efficacy of immune checkpoint inhibitors against STAD.